ANALISIS KUALITAS AIR YANG AIR DISTRIBUSI KE PELANGGAN PADA ZONA BANJARMASIN UTARA PAM BANDARMASIH - Ridho, Muhammad Rasyid; Rahman, Mijani; Yunita, Rizmi; Sofarini, Dini (Universitas Lambung Mangkurat, 2024)
There are several processes involved in the treatment of clean water, namely filtering, sedimentation, coagulation, flocculation, filtration, and disinfection. These processes are utilized by PAM Bandarmasih at the Water Treatment Plant II (IPA II) situated on Jalan Pramuka. The objective of the research is to analyze the quality of water distributed to the North Zone of Banjarmasin by PAM Bandarmasih. The research location was intentionally chosen (purposive sampling) within the Bandarmasih PAM area, encompassing the raw water sources from the Tabuk River, IPA 1, and IPA 2 in the North Banjarmasin zone. The Tabuk River watershed serves as a tributary of the Martapura River, which is utilized as a water source to fulfill the daily needs of the people. The data analysis technique employed to address the research objectives involves analyzing the quality of distributed clean water using the storet method. Evaluation of the water quality distributed to customers in the North Banjarmasin PAM Bandarmasih zone leads to the conclusion that both the quality of raw water and treated water as a whole meet the quality standards outlined in accordance with PERMENKES Regulation Number 2 of 2023. The assessment of clean water quality distributed is based on the water quality storet method, indicating that the clean water distributed by PAM Banjarmasih originates from the lightly polluted AD Mufti River, with a total score of (-9).